2009 12th Euromicro Conference on Digital System Design, Architectures, Methods and Tools 2009
DOI: 10.1109/dsd.2009.157
|View full text |Cite
|
Sign up to set email alerts
|

A Fast SOP Minimizer for Logic Funcions Described by Many Product Terms

Abstract: We introduce a fast and efficient minimization method for functions described by many (up to millions) product terms. The algorithm is based on processing a newly proposed efficient representation of a set of product terms -a ternary tree. A significant speedup of the look-up of the term operation is achieved, with respect to a standard tabular function representation. The minimization procedure is based on a fast application of basic Boolean operations upon a ternary tree. Minimization of incompletely specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Boolean functions minimization using a triple tree, in which basic Boolean operations are applied, is considered in [12]. The method is designed to minimize Boolean func tions with a large number of variables with the support of minimizing incompletely specified functions.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…Boolean functions minimization using a triple tree, in which basic Boolean operations are applied, is considered in [12]. The method is designed to minimize Boolean func tions with a large number of variables with the support of minimizing incompletely specified functions.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…The advantage of DRedSOP circuits is that their depth is bounded, since the number of logic levels is equal to three. Moreover, circuits with a bounded number of levels, three or four ( [Perkowski 1995;Sasao 1995;Dubrova and Ellervee 1999;Debnath and Sasao 1999;Luccio and Pagli 1999;Debnath and Vranesic 2003;Ishikawa et al 2004]), often result to be much more compact in area than classical two level logic forms ([McGeer et al 1993; Coudert 1994; Fišer and Toman 2009]).…”
Section: Introductionmentioning
confidence: 99%
“…However, other work has shown that optimal k-anonymity can be approximated in reasonable time for large datasets to within O(k log k) when k is constant, though runtime for such algorithms is exponential in k. It has been shown that Facebook data can be modeled as a Boolean expression which when simplified measures its k-anonymity [13]. Section VIII discusses how such expressions, constructed from Facebook data, are of a type that can be simplified in linear time by certain logic minimization algorithms [14].…”
Section: Related Workmentioning
confidence: 99%
“…A minimization method developed at Czech Technical University has been shown to scale linearly for two-level logic minimization problems in which there are many terms (millions) and far fewer literals [14]. This algorithm is being evaluated for use in calculating q due to the fact that when there are n users (literals) and m attribute values, the number of terms to be minimzed is bounded by O(n n 4 ) when m ≥ √ n, otherwise when m < √ n the number of terms is bounded by O(( n m ) m ).…”
Section: Current Workmentioning
confidence: 99%